Microplastic pollution in seabed sediments at different sites on the shores of Istanbul-Turkey: Preliminary results - Erkan, Hanife Sari; Turan, Nouha Bakaraki; Albay, Meric; Engin, Guleda Onkal (ELSEVIER SCI LTD, 2021)
Despite recent increase in microplastics-related studies, little is known about their abundance in seabed sediment areas. However, the quantity of microplastics (MPs) in sediments is imperative for an overall understanding of worldwide MPs pollution. To address the above-mentioned gap, this study was performed on 43 seabed sediment stations from the Marmara Sea of Turkey. Studied stations vary between marine (MRN), pier (PIER), stream (STR), sea discharge (SD), and deep-sea discharge (DSD) stations. Collected seabed sediment samples were analyzed for MPs abundance, shape, size and color distribution. Besides, an investigation on the effect of sea depth on MPs' total abundance, size, and shape was investigated using Pearson's and Spearman's product momentum correlation coefficient. Empirical data analysis showed that the highest MPs abundance at STR stations changed between 1956.5 +/- 3031.8 and 3256.2 +/- 5168.2 particle/kg (dry weight: d.w.) for small MPs particles (SMP) and large MPs particles (LMP), respectively. Contrarily, the lowest abundance was found as 224.8 +/- 423.05 and 287.68 +/- 218.6 particle/kg (d.w.) for SMP and LMP fractions, respectively at DSD stations. The MPs abundance were found at 5 categorized stations in the following order; STR>PIER>MRN>SD>DSD, noted that the highest MPs quantity was found at STR-6 station located in Golden Horn. The isolated MPs were predominantly filament and fragment in shape (42.34 +/- 6.10% and 33.91 +/- 6.92%), blue and white in color (40.46 +/- 4.66% and 24.75 +/- 3.83%). Mean MPs abundance was determined to be 1957.37 +/- 4079.96 particle/kg (d.w) at all 43 stations and sizes between 1 and 5 mm was found to be predominant at depths between 5 and 71m. Furthermore, a negative correlation was found between sea depth and parameters such as total MPs abundance, shape, and size. The overall results revealed the widespread presence of MPs in the seas surrounding Istanbul.
Keywords: Microplastics; Seabed sediments; Marmara sea; Istanbul; Turkey; YELLOW SEA; SURFACE SEDIMENTS; PLASTIC DEBRIS; MARINE; ORGANISMS; ABUNDANCE; FATE; IDENTIFICATION; PARTICLES; IMPACTS; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology